An extensive analysis and environmental sustainability applications of multifunctional biochar developments: Current trends and technological advances - Farah Amalina, .; Santhana, Krishnan; Zularisam, Ab Wahid; Mohd Nasrullah, Zulkifli (Elsevier Ltd, 2025)
This review highlights the multifunctional applications, recent trends, and technological advancements of biochar (BC), a carbon-rich material produced through biomass pyrolysis. BC has emerged as a promising solution to environmental and agricultural challenges. The manuscript examines key production methods, such as slow pyrolysis, fast pyrolysis, and gasification, and their effects on BC’s physical, chemical, and structural properties. It explores BC’s applications in soil improvement, water treatment, waste management, and renewable energy. Recent innovations, including nano-BC, BC composites, advanced pyrolysis techniques, and feedstock diversification, are discussed alongside the importance of quality and safety standards. This review emphasizes BC’s versatility and potential to drive sustainable solutions, offering insights for future research and development.